Secretoglobin Superfamily Protein SCGB3A2 Deficiency Potentiates Ovalbumin-Induced Allergic Pulmonary Inflammation. (27th August 2014) - Kido, Taketomo; Yoneda, Mitsuhiro; Cai, Yan; Matsubara, Tsutomu; Ward, Jerrold M.; Kimura, Shioko
Abstract : Secretoglobin (SCGB) 3A2, a cytokine-like secretory protein of small molecular weight, which may play a role in lung inflammation, is predominantly expressed in airway epithelial cells. In order to understand the physiological role of SCGB3A2, Scgb3a2 −/− mice were generated and characterized. Scgb3a2 −/− mice did not exhibit any overt phenotypes. In ovalbumin- (OVA-) induced airway allergy inflammation model, Scgb3a2 −/− mice in mixed background showed a decreased OVA-induced airway inflammation, while six times C57BL/6NCr backcrossed congenic Scgb3a2 −/− mice showed a slight exacerbation of OVA-induced airway inflammation as compared to wild-type littermates. These results indicate that the loss of SCGB3A2 function was influenced by a modifier gene(s) in mixed genetic background and suggest that SCGB3A2 has anti-inflammatory property. The results further suggest the possible use of recombinant human SCGB3A2 as an anti-inflammatory agent.